The effects of vegetarian diets on bone health: A literature review - Falchetti, Alberto; Cavati, Guido; Valenti, Roberto; Mingiano, Christian; Cosso, Roberta; Gennari, Luigi; Chiodini, Iacopo; Merlotti, Daniela (Frontiers in Endocrinology, 2022)
In these recent years many people are adopting a vegetarian type diet due to the numerous positive health effects of this regimen such as the reduction of the incidence of many chronic disorders like diabetes, hypertension, obesity and cancer. However this diet is quite restrictive and so it could be possible to have a deficiency in some specific nutrients, increasing the risk of osteoporosis and fractures. Although there are conflicting results on the effects of the vegetarian diet on bone health and fracture incidence, it is always recommendable in vegetarian people to have an adequate intake of calcium and vitamin D, through an increased intake of supplements, natural and fortified foods, an adequate intake of protein, fruit, vegetables, as well as vitamin B12. The aim of this literature review is to revise the actual knowledge of the effect of some nutrients and vegetarian diets on bone health.